Perancangan Media Pembelajaran Pengenalan Hewan Laut Berbasis Multimedia Interaktif - Latifah Nur Fitriana; Riyan Abdul Aziz (Repeater : Publikasi Teknik Informatika dan Jaringan, 2024)
Technology is developing so quickly that it may have a significant impact on the way teaching and learning are done. Interactive multimedia-based learning materials play an important role in the teaching and learning process. The availability of educational media can make teaching easier for teachers and increase students' learning motivation. This research focuses on designing multimedia-based interactive learning media for introducing marine animals. Researchers found the problem that the learning process at TK BA Aisyiyah Grogol 2 still uses the lecture method and does not use technology. This causes students' interest in learning to decrease. The method applied in designing this learning media is the ADDIE method. The result of this research is an interactive learning media design that uses multimedia. It is hoped that this learning media can increase students' interest in learning and the learning process will become easier and more effective.